The Influence of Entrepreneurial Spirit towards Farm Performance of Fish Cultivation Nile Tilapia, Sleman Regency, Indonesia - Mulyaningtiyas, Ratna Dewi (Prosiding Seminar; 2019: 2019 International Conference of Interdisciplinary SciencesDO - 10.32503/prosidingseminar.v0i0.6, 2019)
Farmers' entrepreneurship is very important as a new approach to improving farm performance is based, among others, on entrepreneurial characteristics. Entrepreneurship is the ability to create and provide value-added products. Fisheries are increasingly in demand because people are becoming aware of the many benefits of fish, especially for health. The objective of this research was to determine the performance of fish cultivation in Nile Tilapia farming. The research location is determined purposively and the total sample is 150 respondents. This methods of data analysis is using analysis of SEM (Structural Equation Modeling). The results showed that Entrepreneurial spirit influences farm performance, so it can develop a tilapia cultivation business as well as income, profits, business feasibility. Members of tilapia aquaculture groups on average have high income and profits, so this business is worthy of the effort.